'History, archaeology and hydraulic engineering' (Bulletin KNOB, 1994)
The confrontation of lock and sluice research with interdisciplinary cooperative models by F. Verhaeghe and H.L. Janssen can be summarized by five propositions which general applicability for interdisciplinary research is to be further tested. Firstly, Verhaeghe and Janssen pay no attention to the possibility that even in research in which interdisciplinary cooperation was not anticipated, the presentation of questions may lead to an interdisciplinary approach. In such a case there is a risk that the presentation of questions and the research object of the other discipline are taken over. However, afterwards the cognizance of the presentation of questions of the other disciplines will result in a more sharply and better-defined presentation of one's own questions in the research. Moreover, influence from other disciplines may make the presentation of questions more profound and give the informative value of one's own sources a wider scope.Secondly, 'interdisciplinary language acquisition' is required for interdisciplinary research. This should be done in a rather deliberate way prior to or during the first phase of the research and calls for experiments with various forms of communication. Thirdly, also due to the use of other sources of information, each discipline requires a different source analysis. For that reason, as a supplement to Janssen, sufficient room should be made in interdisciplinary research for the 'intradisciplinary phase'. In this phase the results of source analysis within the particular discipline and the intradisciplinary interpretation preceding the translation into other disciplines are tested.In the fourth place, the various phases of an interdisciplinary research project are run through several times cyclically, consequently, in a genuine research process the two complementary levels of Verhaeghe and Janssen recur a number of times. Finally, since interdisciplinary language acquisition is required for interdisciplinary communication, an interdisciplinary approach may delay the research process. However, some presentations of questions can only be answered in an interdisciplinary way. This particularly applies to the medieval history of hydraulic engineering with respect to which so few written, historical sources have been passed down to us.